Peningkatan Kualitas Guru dengan Pelatihan Google Classroom sebagai Media Alternatif School From Home pada SMK Puspita Persada Jakarta Selatan - Pudoli, Ahmad; Hardjianto, Mardi; Setiono, Devit (LPPM Universitas Bina Sarana Informatika, 2021)
The COVID-19 pandemic in early 2020 is causing major changes in community activities today. Starting from trade, economy, jobs as well as in the world of education. Schools must participate in preventing the spread of the COVID-19 virus by changing teaching patterns in accordance with the instructions of the Ministry of Education and Culture of the Republic of Indonesia, where teaching and learning activities are carried out from home. Puspita Persada Vocational High School participated in the success of the government program by changing the teaching pattern from home. However, because this instruction was given quickly, SMK Puspita persada has not prepared technically thoroughly in teaching and learning. Currently the teaching method is done using WhatsApp Group and email. Of course, this method still needs to be developed so that the delivery of teaching materials is more perfect. The purpose of this activity is to provide training using Google's facility, Google ClassRoom, to improve the ability of teachers to deliver and deliver materials to the maximum and based on better technology. The method that will be done in this activity is face-to-face training (if possible) but still apply physical distancing in the presentation of the material. This method will be adjusted at the time of implementation in accordance with existing conditions. Based on Abdimas activities, it can be concluded that google classroom training provides tremendous benefits for teachers. Teachers are very enthusiastic and interested in using google classroom, teachers know applications that can be used as a learning medium, teachers can be easier to manage classes, save time, and give examples to students to maintain the environment by reducing paper use.